REMEDIASI MISKONSEPSI MENGGUNAKAN STRATEGI PREDICT-OBSERVE-EXPLAIN BERBANTUAN LABORATORIUM VIRTUAL PADA MATERI RANGKAIAN LISTRIK SEARAH - Arinata, Dwi; Sitompul, Stepanus Sahala; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractAbstract: This research was a pre-experimental design of one group-pretest posttest design to find out the effectiveness of remediation of studentsâ€™ misconceptions about direct current circuit using predict-observe-explain (POE) strategy. The data were collected through diagnostic test in form of six multiple choices along with reasoning which led to have reabilty as of 0,5. There were 37 students of grade IXE of SMP Negeri 7 Pontianak involved in this research as research sample. They were chosen based on intact group random sampling. Based on the profile of misconception before and after remediation was applied, the value of pre-test and post-test showed difference as of 39%. The mean decrease of misconception for all questions based on the McNemar test results obtained x2 count (11.7)> x2 table (3,84), then there was a significant decrease of misconception after remediation was done using POE strategy. In addition, the effectiveness of remediation using the POE strategy was obtained using Cohen's Effect size of 1.65. This research is expected to be used as an alternative remediation activity for students to be able to overcome misconception experienced by students.Keywords: Remediation, Misconception, Predict-Observe-Explain (POE) strategy, Direct Current Circuit